Strengthening Character Education Based on Local Wisdom in Learning IPS - Dany Miftah M. Nur; Abi Amar Zubair (Department of Tadris IPS FITK IAIN Syekh Nurjati Cirebon, 2022)
Abstract: The purpose of this research is to reveal the local wisdom of Lau village in Dawe, Kudus as a social study learning resource for strengthening the character education of students at MTs NU Sunan Muria Kudus. This research type is field research with a descriptive qualitative approach in which the research subjects are social studies teachers, eighth grade students, and the Lau village community in Dawe, Kudus. Data collection techniques are using interviews, observation, and documentation. The analysis used is data collection, data reduction, data display, and drawing conclusions. The results of this research indicate local wisdom in the form of Tapa Ngeli and Pager Mangkok and the relevance of both local wisdom with social studies learning resources at MTs NU Sunan Muria can be seen in the cultural function academically and practically according to basic competences and GPA as well as the implementation of strengthening character education through local wisdom of Lau village in Dawe, Kudus with social studies learning activities starting with the opening. The main activities include literacy, collaboration, and communication activities. In the end, there are material concluding and advising. For the closing, ended with prayers and parting. In conclusion, local wisdom forms of Lau village in Dawe, Kudus can become a social study learning resource that strengthens the character of the students at MTs NU Sunan Muria Kudus. Keywords: Character Education, Local Wisdom, Social Studies Learning Resources Abstrak: Penelitian ini bertujuan untuk mengetahui kearifan lokal Desa Lau Dawe Kudus sebagai sumber belajar IPS untuk penguatan pendidikan karakter peserta didik di MTs NU Sunan Muria Kudus. Penelitian ini menggunakan jenis penelitian lapangan dengan pendekatan kualitatif deskriptif dengan subjek penelitian guru IPS, peserta didik kelas VIII, dan masyarakat Lau Dawe Kudus. Teknik pengumpulan data dengan wawancara, observasi, dan dokumentasi. Analisis yang digunakan yaitu pengumpulan data, mereduksi data, mendisplay data, dan penarikan kesimpulan. Hasil dari penelitian ini menunjukkan kearifan lokal berupa tapa ngeli dan pager mangkok dan relevansi kearifan lokal tapa ngeli dan pager mangkok dengan sumber belajar IPS di MTs NU Sunan Muria terlihat dalam fungsi budaya secara akademis dan praktis sesuai antara KD dan IPK serta implementasi penguatan pendidikan karakter melalui kearifan lokal Lau Dawe Kudus dengan kegiatan pembelajaran IPS dimulai dengan pembukaan. Kegiatan inti dengan kegiatan literasi, collaboration, dan communicaty. Akhir, ada kesimpulan materi dan pemberian nasehat. Penutup, diakhiri doa dan salam. Simpulannya bentuk-bentuk kearifan lokal Desa Lau Kudus dapat menjadi sumber belajar IPS yang menguatkan karakter peserta didik di MTs NU Sunan Muria. Keywords: Pendidikan Karakter, Kearifan Lokal, Sumber Pembelajaran IPS